2008
DOI: 10.1093/eurpub/ckn115
|View full text |Cite
|
Sign up to set email alerts
|

Price sensitivity and smoking smuggled cigarettes

Abstract: Low-income, poorly-educated smokers are most likely to purchase smuggled cigarettes. To alter such behaviour, government must understand the motivations and opinions of this population and create marketing messages targeted specifically to their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…This conclusion contradicts those of previous studies (Hyland et al, 2005;Lee et al, 2009) which suggest that demand for illicit tobacco is driven by its low price relative to legal forms of tobacco. Hyland et al (2005) found that higher cigarette prices influence many price-sensitive smokers to seek lower priced or tax-free cigarette sources as a strategy to continue smoking.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This conclusion contradicts those of previous studies (Hyland et al, 2005;Lee et al, 2009) which suggest that demand for illicit tobacco is driven by its low price relative to legal forms of tobacco. Hyland et al (2005) found that higher cigarette prices influence many price-sensitive smokers to seek lower priced or tax-free cigarette sources as a strategy to continue smoking.…”
Section: Discussioncontrasting
confidence: 99%
“…A study of Taiwanese smokers (Lee, Chen, Chen, & Jeng, 2009) incorporated a measure to capture the price sensitivity of a smokers' decision to buy smuggled cigarettes, and found that low income and low levels of education are characteristic of current tobacco smokers who are more likely to be inclined to smoke smuggled cigarettes given a price increase of legal cigarettes. Nevertheless, investigation into motivating factors other than the favourable price difference between legal and illicit tobacco products is limited.…”
Section: Illicit Tobacco Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…That strongly supports an inverse association between price and cigarette smoking. Lee J. M. et al (2009) have confirmed in Taiwan that low-income, poorly-educated smokers are most likely to purchase smuggled cigarettes when faced with the rising costs of legal cigarettes. Iglesiasa R. et al (2007) studied the smoking situation in Brazil, and the importance of the tobacco control program in reducing smoking in the country.…”
Section: Introductionmentioning
confidence: 93%
“…While some research argues that there is a positive relationship between consumer income and cigarette consumption (Andrews and Franke, 1991), others demonstrate the opposite (Baltagi and Levin 1986;Olgloblin and Brock, 2003). Some suggest that lower income consumers are more likely to smoke (Ahrens 2009), are more sensitive to prices (Lois et al 1998;Gruber, Sen et al, 2003) and are more inclined to resort to contraband cigarettes (Lee et al 2009), while others demonstrate that there is no significant difference between income groups (Farrelly, Engelen et al, 2008). At the macro level, the level of economic development of the region or country, in other words its level of richness, has been shown to affect cigarette consumption such that poorer countries tend to have higher smoking rates than richer ones (Chapman et Richardson 1990;van der Merwe et Abedian, 1999;Lance, Akin et al, 2004).…”
Section: P4mentioning
confidence: 99%